STRATEGI PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI HIMPUNAN DI MASA PANDEMI COVID-19 - Latifah, Neng Istiqomah Wardah; Sutirna, Sutirna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze the use of mathematical problem-solving strategies used by student in solving math problems in the form of story problem on set materials when learning must be done online. This research using qualitative approach-descriptive methods. The research was conducted in grade VII SMP Negeri 2 Telukjambe Timur with 30 students. The instrument in this study consisted of two items problem solving abilities on the set material. The research subject were analyzed by referring to indicators of mathematical problem solving strategies according to Polya and Pasmep which consisted of trial and error strategies, making pictures or diagrams, finding pattern, and logical thinking. The data analysis technique in this research is using descriptive analysis which consists of the stages of reducing the data, presenting the data and drawing conclusions. The result showed that of the 30 students who took the test via WhatsApp as a media, most of the student completed the test by implementing a trial and error strategy. As for the details of using strategy in completing the test were as many as 46,60% of the students solve the problem with a trial and error strategy; 6,65% of the students with strategies to make pictures or diagrams; 23,30% of the students with strategies to find patterns, and 23,30% of the students with strategies think logically.